Redesigning the patient classification system in China: A pilot study. (28th December 2017) - Bai, Yamei; Yao, Aaron; Song, Yulei; Xu, Guihua
Abstract: The current prototype patient classification system in China has not been updated for over six decades. In the present study, we adopted a hybrid patient classification method using both disease severity and activities of daily living scores to classify patients. The time motion approach was used to measure the direct nursing time of 551 general acute care patients. We found that patients in old Categories according to ability of self‐care and disease severity 1–4 received approximately 7.1, 4.6, 3.4, and 4.5 h of direct nursing care, and the number of hours was not significantly different between Categories 2, 3, and 4. In contrast, patients in new Categories 1–4 received approximately 10.1, 6.9, 4.4, and 2.4 h of direct nursing care in 24 h. The nursing hours were significantly different between all pairings of the new categories. The new classification system can be used to make nursing care assignments and adjust staffing.